MOTIVES OF LAJJA GAURI IN INDIAN ART: A STUDY - Jee, Ramakant; Dey, Subrata (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Art is the expression of thoughts and feelings, which inspires by the events around oneself, it takes support of various mediums to express ones feelings and emotions. The matriarchal nature of the society in ancient times gives stability to our thinking. The reason must have been that men would have been responsible for collecting the resources for living in the society and in their absence it would have been the responsibility of women to run the social system. Almost this tradition is more or less maintained till today. Such traditions and conditions of contemporary society are depicted through various mediums of art. In these mediums, it is necessary to collect some important information regarding the marking of men and women, some are marked according to the plot described in mythology and some are independent. The detail study is discussed below with reference.